PERAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM PEMBENTUKAN KARAKTER SISWA KELAS IX DI SMP PLUS HIDAYATUL MUBTADIIN SINGOSARI - Syihabuddin Najib; Muhammad Hanief; Ari Kusuma Sulyandari (VICRATINA, 2022)
School is a place where students learn to gain knowledge, especially related to character education. Character education is of course very important so that students have good character in good behavior towards teachers and parents. This research was conducted at SMP Plus Hidayatul Mubtadi'in Singosari which is often called SMP Kembang is a private school located in Singosari sub-district. In fact, there are still many characteristics of students who often violate school rules such as being late, sleeping in class, uniforms that are not on schedule and the way they speak is also impolite. So this is an important concern for researchers to make further observations regarding the role of PAI teachers in the formation of these characters. The method used is qualitative method, data collection techniques used are observation, interviews and documentation. The results obtained by the strategy used are habituation, example, giving motivation, advice or advice. Inhibiting factors are promiscuity between peers, excessive use of cellphones.